2012
DOI: 10.1002/aur.1222
|View full text |Cite
|
Sign up to set email alerts
|

Motor Learning Relies on Integrated Sensory Inputs in ADHD, but Over‐Selectively on Proprioception in Autism Spectrum Conditions

Abstract: Lay Abstract Children with autism spectrum disorder (ASD) show deficits in development of motor skills, in addition to core deficits in social skill development. In a previous study (Haswell et al., 2009) we found that children with autism show a key difference in how they learn motor actions, with a bias for relying on joint position rather than visual feedback; further, this pattern of motor learning predicted impaired motor, imitation and social abilities. We were interested in finding out whether this alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
136
1
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(164 citation statements)
references
References 66 publications
20
136
1
7
Order By: Relevance
“…In another example of better than normal performance in autism, and the inspiration for our current study, we found that children with ASD showed greater than normal generalization of force field adaptation in intrinsic, or proprioceptive, coordinates (Haswell et al, 2009;Izawa et al, 2012b). In other words, after learning to fully compensate for a force field, children with ASD expressed that learning better than controls in a new workspace that was proprioceptively similar to the original workspace.…”
Section: Sensitivity To Errorsupporting
confidence: 54%
See 2 more Smart Citations
“…In another example of better than normal performance in autism, and the inspiration for our current study, we found that children with ASD showed greater than normal generalization of force field adaptation in intrinsic, or proprioceptive, coordinates (Haswell et al, 2009;Izawa et al, 2012b). In other words, after learning to fully compensate for a force field, children with ASD expressed that learning better than controls in a new workspace that was proprioceptively similar to the original workspace.…”
Section: Sensitivity To Errorsupporting
confidence: 54%
“…In a recent series of studies we examined motor learning in ASD, focusing on a reaching task in which the children learned to compensate for a perturbation. We found that children with ASD constructed an internal model that was different than healthy controls, potentially relying more than normal on proprioception, as evidenced by their generalization patterns (Haswell et al, 2009;Izawa et al, 2012b). In contrast, children (Johnson et al, 2013) and adults (Mosconi et al, 2013) with ASD showed slower learning in a saccade adaptation paradigm, in which errors were purely visual in nature.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Deficits in motor adaption implicate the cerebellum, where cell abnormalities in the cerebellar vermis and hemispheres are a robust feature of ASC (Fatemi et al, 2012;Rogers et al, 2013). Several studies suggest that children with ASC rely on proprioceptive feedback for motor adaptation and are impaired when learning motor skills through visual input alone (Izawa et al, 2012;Mostofsky & Ewen, 2011;Sharer, Mostofsky, Pascual-Leone, & Oberman, 2015;Vanvuchelen et al, 2007;Wild, Poliakoff, Jerrison, & Gowen, 2012). Hyposensitivity and hypersensitivity to visual and proprioceptive feedback respectively is indeed correlated with abnormalities in the anterior, sensorimotor aspect of the cerebellum in children with ASC (Marko et al, 2015).…”
Section: The Neuroanatomical Correlates Of Movement Impairmentmentioning
confidence: 99%
“…This result was inferred to indicate flawed cerebellum vermis. The cerebellum vermis plays a vital role in maintaining a consistent accuracy of saccades and correcting systematic errors in saccade amplitudes [14]. In a second E.O.G study, Minshew, Luna and Sweeney [15] recorded the saccade velocity, latency and accuracy of 26 adolescents with ASD using a visually guided saccade.…”
Section: B Saccadic Motion Of the Eyesmentioning
confidence: 99%